2015
DOI: 10.7566/jpsj.84.054701
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ferroelectric Distortion on Thermopower in BaTiO3

Abstract: We present a strategy for increasing thermoelectric performance by invoking ferroelectric distortion in a transitionmetal oxide. By using an ab initio calculation approach with the Boltzmann transport equation, a large Seebeck coefficient is calculated in n-type BaTiO 3 . The polar structural distortion causes the peculiar dispersion of the lowest conduction band, which enhances the Seebeck coefficient along the polar direction. A microscopic mechanism of carrier concentration dependence of the Seebeck coeffic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Magnons and paramagnons give a similar drag effect like phonons, leading to an extra S from the diffusion part. , These methods demonstrate the possibility of finding high-performance TE materials in magnetic materials . The polar crystal distortion in BaTiO 3 creates asymmetries in the Fermi surfaces and results in a considerable enhancement of S along the polar direction, paving a new way for exploring high S in ferroelectric oxides with huge electric polarization . Some are based on specific physical mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnons and paramagnons give a similar drag effect like phonons, leading to an extra S from the diffusion part. , These methods demonstrate the possibility of finding high-performance TE materials in magnetic materials . The polar crystal distortion in BaTiO 3 creates asymmetries in the Fermi surfaces and results in a considerable enhancement of S along the polar direction, paving a new way for exploring high S in ferroelectric oxides with huge electric polarization . Some are based on specific physical mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…36 The polar crystal distortion in BaTiO 3 creates asymmetries in the Fermi surfaces and results in a considerable enhancement of S along the polar direction, paving a new way for exploring high S in ferroelectric oxides with huge electric polarization. 59 Some are based on specific physical mechanisms. It was found that superparamagnetic nanoparticles in Ba 0.3 In 0.3 Co 4 Sb 12 could contribute to S enhancement through an increased scattering parameter.…”
Section: ■ Conclusion and Perspectivesmentioning
confidence: 99%